2020
DOI: 10.1039/d0dt02949a
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic frameworks decorated with free carboxylic acid groups: topology, metal capture and dye adsorption properties

Abstract: In this report, metal organic frameworks (MOFs) are designed and tuned for the structural variations in order to induce the metal capture which in turn directs the dye adsorption properties....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 65 publications
2
33
0
Order By: Relevance
“…At present, the treatment methods of dye wastewater mainly contain coagulation, electrolysis, oxidation, photocatalytic degradation and adsorption, etc., [36–39] and adsorption has become the preferred treatment method for researchers due to simple operation [40] . Furthermore, uranyl functional complexes also have adsorption properties to dyes, which has been reported in previous literatures [41] . For example, Prof. Fu's group prepared polyamine‐based cyclophosphazene hybrid (PCP‐NH 2 ) hollow microcapsules to absorb dyes [42] .…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…At present, the treatment methods of dye wastewater mainly contain coagulation, electrolysis, oxidation, photocatalytic degradation and adsorption, etc., [36–39] and adsorption has become the preferred treatment method for researchers due to simple operation [40] . Furthermore, uranyl functional complexes also have adsorption properties to dyes, which has been reported in previous literatures [41] . For example, Prof. Fu's group prepared polyamine‐based cyclophosphazene hybrid (PCP‐NH 2 ) hollow microcapsules to absorb dyes [42] .…”
Section: Introductionsupporting
confidence: 62%
“…[40] Furthermore, uranyl functional complexes also have adsorption properties to dyes, which has been reported in previous literatures. [41] For example, Prof. Fu's group prepared polyamine-based cyclophosphazene hybrid (PCP-NH 2 ) hollow microcapsules to absorb dyes. [42] In order to further broaden the application fields of uranyl complexes, in this work, it is found that four novel uranyl functional complexes have potential adsorption properties to Methylene Blue, Rose Red, Eosin and Coomassie Brilliant Blue.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4a, due to the differences in channels and functional groups, UPC‐60‐Cl and UPC‐60‐NH 2 show specific dye adsorption effects. Among them, UPC‐60‐Cl has an excellent adsorption effect on CV, RHB, and MO, with the maximum adsorption capacity reaching 147.2, 100.3, and 220.9 mg g −1 , respectively, which is comparable to the Fe@Cu‐MOF‐2COOH (MO: 225.1 mg g −1 ) [48] and higher than Cd‐based MOF (MO: 166.7 mg g −1 ), [49] but lower than PCN‐222 (MO: 589 mg g −1 ) [50] . This adsorption performance may be due to the multiple channel structures and environments having different adsorption effects on the dye molecules of different sizes.…”
Section: Resultsmentioning
confidence: 92%
“…The metal ions were penta-coordinated and adopted a square pyramidal geometry (τ = 0.05) with O7 from the oximic group occupying the apical position [78]. The framework in 3 forms a 3-c uninodal net [79][80][81] of hcb topology (Figure 4, left) with the layers being parallel to the (1,0,1) plane [82][83][84]. Taking also into account the intermolecular interactions between the Hbtc 2-ligands, the resulted 3D framework exhibited a utp topological type (Figure 4, right) [85][86][87].…”
Section: Synthetic Discussionmentioning
confidence: 99%